Ecological Health Risk of Buriganga River, Dhaka, Bangladesh - Ali, Mohd. Yousuf; Amin, Md. Nurul; Alam, Khairul (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
The efforts of modern civilization to create an environment to meet human aspirations have successfully resulted in constant improvements of our lifestyle, but it has increased risks to human and ecological health. This situation has motivated many scientists throughout the world to analyze the environmental factors that can affect our health or ecology and to calculate the levels of risk. In Bangladesh development activities and utilization of the river pose a great threat to the health of the existing natural environmental system, particularly for the important river Buriganga of the capital city, Dhaka, due to the pollution of the river water. A study was carried out to observe the ecological health hazards of the Buriganga river and their risk to human health. Several random samples of water were collected from different spots on the river from September to December 2006. The samples were analyzed to determine water quality and associated environmental health risks. The study revealed that the water is high in biological oxygen demand (BOD), chemical oxygen demand (COD), phosphate (PO4 -3), ammonia, organic matters and nutrients, etc. It also revealed huge environmental health risks and possible ecological disruption of this river. Finally, the research recommends a sustainable policy framework on how the pollution could significantly be reduced by using different appropriate measures. Key words: Environmental health risk, ecological disruption, sustainable policy, water quality, Buriganga river, Bangladesh doi: 10.3126/hn.v3i0.1915 Hydro Nepal:Journal of Water, Energy and Environment Issue No. 3, July 2008. Page: 25-28